A dynamic co-expression approach reveals Gins2 as a potential upstream modulator of HNSCC metastasis - Nasibeh Khayer; Samira Shabani; Maryam Jalessi; Mohammad Taghi Joghataei; Frouzandeh Mahjoubi (Scientific Reports)
Abstract Head and neck squamous cell carcinoma (HNSCC) is an aggressive cancer that is notably associated with a high risk of lymph node metastasis, a major cause of cancer mortality. Current therapeutic options remain limited to surgery supplemented by radio- or chemotherapy; however, these interventions often result in high-grade toxicities. Distant metastasis significantly contributed to the poor prognosis and decreased survival rates. However, the underlying molecular mechanisms remain poorly understood. Disease-related “omics” data provide a comprehensive overview of gene relationships, helping to decode the complex molecular mechanisms involved. Interactions between biological molecules are complex and highly dynamic across various cellular conditions, making traditional co-expression methods inadequate for understanding these intricate relationships. In the present study, a novel three-way interaction approach was employed to uncover dynamic co-expression relationships underlying the metastatic nature of HNSCC. Subsequently, the biologically relevant triples from statistically significant ones were defined through gene set enrichment analysis and reconstruction of the gene regulatory network. Finally, the validity of biologically relevant triplets was assessed at the protein level. The results highlighted the “PI3K/AKT/mTOR (PAM) signaling pathway” as a disrupted pathway involved in the metastatic nature of HNSCC. Notably, Gins2, identified as a switch gene, along with the gene pair {Akt2, Anxa2}, formed a statistically significant and biologically relevant triplet. It suggests that Gins2 could serve as a potential upstream modulator in the PAM signaling pathway, playing a crucial role in the distant metastasis of HNSCC. In addition, survival analysis of significant switch genes indicated that two genes, C19orf33 and Usp13, may be especially important for prognostic purposes in HNSCC.